Long-term survival of the transplanted kidney and the clinical relevance of donor-specific antibodies - Svobodova, Eva (Array, 2020)
The aim of our study was to evaluate the relevance of donor-specific antibodies (DSA) as defined by solid-phase single-antigen (SA) assays for predicting long-term graft survival after kidney transplantation. Sera from 132 kidney transplant recipients were retrospectively tested before, 3, 6 and 12 months after transplantation. The incidence of rejection and graft survival was followed up for 7 years. We found 29 episodes of acute cellular rejection (CR), 21 cases of antibody-mediated rejection (AMR) and 18 graft failures due to immunological reasons. Pre-transplant DSA and DSA three months after transplantation correlated with an increased rate of AMR and impaired graft function. After the fourth year, recipients with persistent DSA were at a higher risk of graft failure (p = 0.0317). Antibody specificity was prevailingly to HLA class I antigens (66.6% DSA, 75% non-DSA). During the first year after transplantation, the number of patients with non-DSA decreased (30.3% to 10.7%), while, due to de novo production of antibodies, the number of DSA positive patients remained constant. Conclusion: Detection of antibodies to HLA antigens using solid-phase assays, especially single-antigen bead technology before and three months after transplantation is predictive for increased incidence of antibody-mediated rejection and impaired long-term kidney graft survival.